Implementasi Media Kopipan Berbasis Model Problem Based Learning sebagai Upaya Peningkatan Hasil Belajar Peserta Didik Kelas II pada Materi Penerapan Nilai-nilai Pancasila - Puspitasari, Herlina Dewi; Purwati, Panca Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research was motivated by the low learning outcomes of class II students at SD Negeri 3 Sidorejo regarding the application of Pancasila values in the family environment. This is because teachers still use the lecture method in delivering material, learning is not yet student-centered, and there is still a lack of use of learning media. The aim of this research is to describe the implementation of Kopipan media based on the Problem Based Learning model as an effort to improve the learning outcomes of class II students in the material on the application of Pancasila values in the family environment and to describe the increase in learning outcomes of class II students on the material on the application of Pancasila values. in the family environment. This research uses a qualitative descriptive type of research. Data collection techniques were carried out using tests and non-tests. The test is carried out by pretest and posttest, while the non-test is carried out by interview and observation. The subjects in this research were class II students at SD Negeri 3 Sidorejo, totaling 14 students. The results of the research show that the Kopipan media based on the Problem Based Learning model can improve the learning outcomes of class II students on the application of Pancasila values in the family environment. This is proven by the increase in the average posttest score of 26.43 from 48.57 at pretest to 75.00 at posttest.